ASSESSMENT OF FINANCIAL MANAGEMENT BY OWN EXPENSES AT HOTEL AND RESTAURANT ENTERPRISES - Ігор Румик; Вікторія Лакіза; Оксана Курило; Наталія Антошкова; Галина Тараненко (Фінансово-кредитна діяльність: проблеми теорії та практики)
Evaluating a management system is always a complex and debatable process, as it is difficult to find an approach that integrates all aspects of management and allows for a comprehensive assessment that reflects the level satisfying all the needs of enterprise management. This also pertains to financial management, which, despite the possibility of using indicators of financial activity of the enterprise, also includes a range of other indicators such as technical support, staff, and more. Considering the existing difficulties, this article aims to propose an integral approach to the assessment of financial management by the own expenses of enterprises. Acknowledging the complexity and individualism of each open socio-economic system, the object chosen is enterprises in the hotel and restaurant sector. Accordingly, it presents a scientific task that involves justifying and applying an approach to assessing the effectiveness of financial management by own expenses at hotel and restaurant enterprises. The research methodology involves the use of general scientific methods such as abstraction, analysis, synthesis, etc. However, the key methods are integral assessment and expert analysis. In combination, they facilitated the identification of the importance of indicators and the obtaining of assessment results. The main result of the study was the identification of operating hotel and restaurant enterprises and, based on their data and information, calculation of indicators which ultimately allowed the calculation and analysis of the dynamic, integral indicator of the effectiveness of financial management by own expenses. The limitation concerns not considering an even broader spectrum of indicators, as the concept of "effectiveness" is extremely broad and our proposed list is not exhaustive.